2019
DOI: 10.1007/s00268-019-05118-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Opt‐out Versus Opt‐in Consent on Deceased Organ Donation and Transplantation (2006–2016)

Abstract: Background Significant numbers of patients in the USA and UK die while waiting for solid organ transplant. Only 1–2% of deaths are eligible as donors with a fraction of the deceased donating organs. The form of consent to donation may affect the organs available. Forms of consent include: opt‐in, mandated choice, opt‐out, and organ conscription. Opt‐in and opt‐out are commonly practiced. A systematic review was conducted to determine the effect of opt‐in versus opt‐out consent on the deceased donation rate (DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 48 publications
0
63
0
6
Order By: Relevance
“…Due to the diversity of the systems and the complexity of the organ donation process, the legal situation and the potential burden of decision for families are not the sole factors explaining varying organ donation rates. Systematic reviews suggest that countries with opt-out systems have higher rates of organ donations after brain death [18], but others showed that there are no differences between opt-in and opt-out systems [19,20] depending on the studies and countries included in the analysis. There are indeed examples of highly successful countries with an opt-in system, such as the USA; however, switching from opt-out to opt-in does not necessarily result in a sustainable increase of organ donation rate [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diversity of the systems and the complexity of the organ donation process, the legal situation and the potential burden of decision for families are not the sole factors explaining varying organ donation rates. Systematic reviews suggest that countries with opt-out systems have higher rates of organ donations after brain death [18], but others showed that there are no differences between opt-in and opt-out systems [19,20] depending on the studies and countries included in the analysis. There are indeed examples of highly successful countries with an opt-in system, such as the USA; however, switching from opt-out to opt-in does not necessarily result in a sustainable increase of organ donation rate [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The development of a legally based social infrastructure clearly affects the increase in organ donation. In particular, the opt‐out systems led to an increase in deceased organ donation 14‐16 . Although no opt‐out system has been introduced, the revision of the law on donating brain‐dead organs in 2010 increased the number of donations from brain‐dead patients, which resulted in an increase in the number of pancreas transplantation procedures, as well as heart 11,17 and lung 18,19 transplantation procedures, in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the implementation of an opt-out system may not automatically translate to an improvement in organ and tissue donations. 32 A systematic review conducted by Ahmad et al 20 showed that opt-out systems increase the donation rate by 21-76% over 5-14 years. However, another review demonstrated a conflicting finding whereby the donation rate was similar between opt-out and opt-in systems, highlighting the need for addressing other barriers to organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…On 20 th May 2020, England has implemented an opt-out system, also known as the Max and Keira’s Law, with an aim to improve the rate of organ and tissue donation, 19, 20 joining countries such as Spain, France and Italy, and many others. Under the new, soft opt-out system, all adults in England are now assumed to be willing organ and tissue donors unless they have registered their intent otherwise.…”
Section: Introductionmentioning
confidence: 99%